So close yet so far: Economic accessibility of Mount Kinabalu / Christy Bidder ... [et al.] - Bidder, Christy; Polus, Reni Cacillia; Jones, Thomas Edward (UiTM Press, 2017)
This study examined the economic accessibility of Mount Kinabalu perceived by the local people of Sabah. Specifically, this study i) examined the concept of willingness to pay (WTP) in light of its association with perceived fee fairness, spending support and place attachment; and ii) analysed the economic and non- economic variables that could potentially pose constraints for the local people to climb Mount Kinabalu and; iii) proved that the inflated total climbing fee had posed a financial barrier for them to access their heritage mountain. The results showed that income is not a significant antecedent of local people's WTP to climb Mount Kinabalu, and the new fee structure itself does not pose a huge barrier for them to access the mountain. The dramatic drop in the number of local climbers following the fee increases is plausibly attributable to their negative perception of fee fairness which lowers their WTP. Additionally, they are more constrained by intrapersonal reasons such as the amount of physical demand required, concerns about health and fitness, and risks involved in climbing than interpersonal or structural factors. When it comes to their spending preferences, they are more supportive of spending on a collective cause (i.e. environmental protection) than an individual cause (i.e. improvement of facilities and services). In sum, cost-related factor does not make Mount Kinabalu less accessible for the local people. What is influencing their WTP is their perception of fee fairness. This study concludes with some recommendations for the management.